Wieże grobowe (Chullpas) z obszaru kompleksu osadniczego w Churajón - Peru oraz zagadnienie ich periodyzacji - Szykulski, Józef (Instytut Archeologii i Etnologii Polskiej Akademii Nauk, 2001)
The site of Churajón (Depto. Arequipa), the largest prehispanic architectural complex in southern Peru (Ryc. 1, 2), is being investigated since 1993 by the Catholic University „Santa Maria" of Arequipa and archaeologists from Poland (cf. Szykulski 1996, 1998, 1998a, 2000, 2000a; Szykulski & Diaz 2000). This article presents the first results of the seasons of 1995/1996 in the burial towers (chullpas) of Torre Ccasa and Mollebaya peak (Ryc. 5-8), probably from the Late Intermediate Period and Late Horizon period
il. ; 29 cm
Keywords: Peru; Extremo Sur; chullpas; Churajón; Ajmara; Inkowie; późny okres przejściowy; horyzont późny; architektura przedkolumbijska; grobowce